Attitudes of Health Workers Towards Management of Hepatitis B Infection in General Hospitals in Kwara State, Nigeria - Abdulrasaq Onaolapo; Abdulraheem Mojisola; Jamiu Oluwatosin; Ijaodola Kikelomo; Jidda Adeola; Onobumeh Margaret (AlQalam Journal of Medical and Applied Sciences, 2024)
Hepatitis B is one of the most dangerous diseases in the world and it has become a serious threat to public health. Health workers are mostly at risk of contracting the disease as they remain the first point of call to the victims. This study examined the attitudes of health workers towards management of HBV infection and the difference in attitudes of health workers based on area of specialization. An ex-post facto research design sampling 412 health workers across different areas of specialization which include doctors, nurses, laboratory scientists and laboratory technicians. Majority of the health workers had negative attitudes towards HBV patients. However, doctors (mean score=3.72) and nurses (mean score=3.54) had mild negative attitudes towards HBV patients, while laboratory scientists (mean score=3.02) and laboratory technicians (mean score=3.04) had the poorest attitudes towards HBV patients. There is need to improve the attitudes of the different cadres of health workers in the state, in order to improve the quality of life of HBV patients and reduce stigma which may impact negatively on patients’ mental health. يعد التهاب الكبد الوبائي (ب) من أخطر الأمراض في العالم وأصبح يشكل تهديدًا خطيرًا للصحة العامة. العاملون في مجال الصحة معرضون في الغالب لخطر الإصابة بالمرض لأنهم يظلون نقطة الاتصال الأولى للضحايا. تناولت هذه الدراسة مواقف العاملين الصحيين تجاه إدارة عدوى فيروس التهاب الكبد B والاختلاف في مواقف العاملين الصحيين على أساس مجال التخصص. تم تصميم بحث بأثر رجعي لأخذ عينات من 412 عاملاً صحياً عبر مجالات التخصص المختلفة والتي تشمل الأطباء والممرضات وعلماء المختبرات وفنيي المختبرات. غالبية العاملين في مجال الصحة لديهم مواقف سلبية تجاه مرضى فيروس التهاب الكبد الوبائي. ومع ذلك، كان لدى الأطباء (متوسط النتيجة = 3.72) والممرضات (متوسط النتيجة = 3.54) مواقف سلبية معتدلة تجاه مرضى فيروس التهاب الكبد B، في حين كان لدى علماء المختبرات (متوسط النتيجة = 3.02) وفنيي المختبرات (متوسط النتيجة = 3.04) المواقف الأكثر فقرًا تجاه مرضى فيروس التهاب الكبد B. . هناك حاجة إلى تحسين مواقف الكوادر المختلفة من العاملين الصحيين في الولاية، من أجل تحسين نوعية حياة مرضى فيروس التهاب الكبد B والحد من الوصمة التي قد تؤثر سلبا على الصحة العقلية للمرضى